Metabolic Syndrome, Anxiety and Depression in a Sample of Italian Primary Care Patients. Issue 5 (May 2018) - Mattei, Giorgio; Padula, Maria Stella; Rioli, Giulia; Arginelli, Lodovico; Bursi, Roberto; Bursi, Serena; Epifani, Antonio Matteo; Pingani, Luca; Rigatelli, Marco; Rosato, Francesca Maria; Sacchetti, Andrea; Galeazzi, Gian Maria; et al.
Abstract : Abstract: This cross-sectional study aimed at measuring the correlation and association of anxiety, depression and comorbid anxiety-depression symptoms with metabolic syndrome (MetS) in a sample of Italian primary care patients who attended their General Practitioner clinics over a 1-month period in 2013. The Hospital Anxiety and Depression Scale (HADS) was used to assess anxiety and depressive symptoms. The sample was made up of 129 patients (57% women; mean age, 61 ± 12 years). The prevalence of MetS varied from 40% (Adult Treatment Panel III-Revised criteria) to 48% (International Diabetes Federation criteria). The prevalence of symptoms of anxiety, depression and comorbid anxiety and depression was, respectively, 26%, 2%, and 15%. MetS (defined according to Adult Treatment Panel III-Revised criteria) was associated with comorbid anxiety-depressive symptoms (odds ratio [OR] = 3.84, 95% confidence interval [CI] = 1.26–11.71), but not with anxiety or depressive symptoms only. Out of the individual components of MetS, enlarged waist circumference was associated with anxiety symptoms (OR = 4.22, 95% CI = 1.56–11.44).